Tomorrow’s Health Data Scientists in the Making: 2 Years of Training & Capacity Building Activities with the Farr Institute - Athanasios Anastasiou; Georgina Moulton; Colin McCowan; Paul Taylor; Catharine Goddard (International Journal of Population Data Science, 2017)
ABSTRACT